Ontologies and Natures: Knowledge about Health in Visual Culture - Gonzalez Rodriguez, Milton Fernando (Lexington Books, 2022)
In Ontologies and Natures: Knowledge about Health in Visual Culture, Fernando Gonzalez Rodriguez argues that visual culture offers insights into how societies perceive the role of nature in pursuits to cure and care for the human body. By using a set of visual surfaces and artefacts as entry points the book sheds light on ideas about nature as a healing source.